2002
DOI: 10.1080/12269328.2002.10541196
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Fracture and Damage in Rock by the Bonded-Particle Model

Abstract: Since potential disturbance of a near-field host rock could adversely affect the stability of underground openings and could possibly change the properties of rock mass, it is very important to evaluate deformation and fracturing characteristics of rock. In this study, PFC 2D modeling as well as laboratory experiments were carried out to study characteristics of deformation and fracturing of rocks under uniaxial and triaxial compressive conditions. Laboratory experiments include stress-strain measurements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…5, left). However when k 2 >1.25 abrupt failure moods are produced, with significant high macroscopic strength (40 to 75), which is similar with Chang's results (CHANG et al, 2002). Figure 6 shows with the increase of ratio k 2 , macroscopic strength increase, and the shear bands seem to be wider.…”
Section: Preliminary Simulation Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…5, left). However when k 2 >1.25 abrupt failure moods are produced, with significant high macroscopic strength (40 to 75), which is similar with Chang's results (CHANG et al, 2002). Figure 6 shows with the increase of ratio k 2 , macroscopic strength increase, and the shear bands seem to be wider.…”
Section: Preliminary Simulation Resultssupporting
confidence: 79%
“…CHANG et al (2002) suggested that another ratio k 2 ¼ F s0 =F r0 may effect the fracture mode, they found that larger k 2 generate brittle failure in uniaxial compression tests. According to rock experiments (ATTEWELL et al, 1976), compressive strength is generally ten times of tensile strength, and shear strength (cohesion) is nearly one to two times of tensile strength.…”
Section: Incorporation Into Lsm and Parameter Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the bonded models, there are different varieties according to interactions being transmitted between bonded particles: Only radial interaction is allowed PLACE, 1993, 1994;MORA et al, 2000;TOOMEY and BEAN, 2000), or only normal and shear forces are present (SCOTT, 1996;CHANG et al, 2002;HAZZARD and YOUNG, 2000), or normal, shear forces and torques are transmitted (WANG et al, 2000(WANG et al, , 2006ODA, 1998, 2000;POTYONDY and CUNDALL, 2004).…”
Section: Introductionmentioning
confidence: 99%